Critical Factors and Their Correlation Affecting Green Industry Performance: Evidences from Small and Medium Enterprises - Noranarttakun, Phurita; Pharino, Chanathip (Applied Environmental Research, 2021)
Large companies have achieved excellent progress toward green production while small and medium enterprises (SMEs) showed limited progress. This research aims to investigate key factors affect different stages of enhancing green industry implementation particularly in SMEs. This study conducted a systematic analysis to offer recommendations to unlock the inhibitors of the green industry. The electronic products and electrical equipment manufacturing industry in Thailand was chosen as a case study. Questionnaire is the main approach to collect primary data from SMEs. The structural equation model is developed to examine correlation and the degree of influencing factors. The model indicated that the latent factors’ influence on the decision-making of SMEs in applying the green industry reflected by the influence of eighteen observable variables and it suggests that the external contexts from stakeholder have a greater influence on the decision-making than the internal context as organizational resources and capabilities. Whereas the level of certification conform with green industry criteria has minor correlation with the decision-making of SMEs. Innovative policy strategy is recommended to create synergy between incentive-based instruments in term of product charges or product tax, subsidies and voluntary measure as product certification are recommended tools to enhance green industry adoption by SMEs.